ILRI highland research: Past activities and future plan - Mohamed-Saleem, M.A. (PERSEE Program, 2000)
The paper identifies poverty and malnutrition, low crop and livestock productivity, widespread land degradation and underutilization of some resources as a major problem of highlands. To tackle these problems, a systems approach to research has been adapted and research has been conducted under the following themes: intentional food/feed production strategies, feed utilisation strategies, livestock mediated soil, water and nutrient management strategies, and spatial integration of system improvement strategies. Specific experimental work done and results achieved are summarised along with a note on future directions.